Republic of Philippines : Mindanao Skills Development Strategy for Poverty Reduction - World Bank (World Bank, Manila, 2020)
This report consolidates written outputs from the Technical Assistance to Support the Elaboration of Mindanao Human Resource Development (HRD) Strategy, which was requested by the Mindanao Development Authority (MinDA) and undertaken by the World Bank under the auspices of the Australia-World Bank Partnership Development Trust Fund. The task was to provide technical assistance and advice to MinDA and other government agencies with HRD related mandate, to develop a medium to long-term skills development strategy for Mindanao, as a critical imperative in securing jobs and enhancing productivity that will redound to poverty reduction in the island-region. Launched in 2017, the World Bank’s Mindanao Jobs Report presented a comprehensive strategy for regional development in Mindanao that will support sustainable peace and development, including job creation. Based on extensive consultations with stakeholders in Mindanao, one of the core recommendations of the report is to boost human development, specifically by addressing the growing skills shortage and rising inequality. Building on these efforts, the World Bank has been working closely with MinDA to generate discussions and identify priority actions on HRD, which were not highlighted in the Mindanao 2020 Peace and Development framework. This report enumerates a set of priority actions to prepare the human resource needed for the development of Mindanao, across its different subregions' contexts and economic corridors. It can serve as both a blue print and a springboard for subsequent collaboration with various development partners to support interventions and long-term programs in Mindanao. On 13 June 2019, MinDA Undersecretary Janet M. Lopoz apprised the Department of Finance (DOF) about a potential partnership with the World Bank to support a long-term program on skills development and employment agenda in Mindanao.